Kedudukan Hukum Adat dalam Sistem Hukum - Mahdi Syahbandir (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: This article aim is to describe regarding customary law in the Indonesia legal system inconnection with Indonesia cionstitusian and other national law level and its impact toward the customary law application in the field.Based on this analytical study can be summerised that: 1). the structure of customary law in Indonesia national law system is the similar position with any other national law. The diffrerence among of them is customary law unrecorded writtenly such as national law; 2). UUD 1945 as Indonesia’s constitusion recognises beside written law also available unwritten law as known with named customary law (hukum adat); 3). UUD 1945 more prioritise written law in form of undang-undang level and other Indonesia’s national law level in creating and managing social live; 4). This reality must be responsed by parliament in craeting Qanun (regional law) in Aceh through accomodating customary law that grow, live and rise in the community, it is caused customary law is an awaranes of law rising in community as populer named living law; and 5). The judicial roles and the finder of law is very strategic in overseeing the legal awaranes occur in the community that must be used as the main consideration in handling particular legal case, therefore judicialprudence is one of legal indentity source whic lives in community.       The Structure of Customary Law In Indonesia’s Legal System